2022
DOI: 10.33102/mjsl.vol10no1.387
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Gejala Rasuah Dan Cabaran Menanganinya Di Malaysia

Abstract: Rasuah dalam kalangan penjawat awam mahupun swasta sering menjadi topik perdebatan di negara-negara luar begitu juga Malaysia. Menurut laporan Suruhanjaya Pencegahan Rasuah Malaysia (SPRM), statistik jumlah tangkapan dari tahun 2014 hingga 2021 telah berlaku kenaikan mendadak sehingga 205 peratus iaitu bersamaan dengan 552 kes kepada 1125 kes. Bahkan Malaysia telah mencatatkan kehilangan hampir RM 1.8 trilion disebabkan kegiatan ini. Pelbagai langkah dan inisiatif telah diambil oleh kerajaan dalam menangani ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…This study aimed to analyse the factors contributing to corruption and the challenges faced by Malaysia in addressing this issue. The research found that internal factors, such as opportunities, personal weaknesses, and a lack of integrity, were the primary causes of corruption (Rahman et al, 2022). External factors included low salaries, financial pressure, excessive workload, and ineffective state policies.…”
Section: Issue 2: Corruption In Politicsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study aimed to analyse the factors contributing to corruption and the challenges faced by Malaysia in addressing this issue. The research found that internal factors, such as opportunities, personal weaknesses, and a lack of integrity, were the primary causes of corruption (Rahman et al, 2022). External factors included low salaries, financial pressure, excessive workload, and ineffective state policies.…”
Section: Issue 2: Corruption In Politicsmentioning
confidence: 99%
“…Individual factors, specifically the psychology of individuals and their upbringing by parents, play a crucial role in this issue (Ismail & Abu Bakar, 2004). Rahman et al (2022) conducted a study on corruption among public and private sector employees, which has been a contentious topic in Malaysia. According to the Malaysian Anti-Corruption Commission (SPRM), the number of arrests surged by 205% from 2014 to 2021, increasing from 552 cases to 1125 cases (Rahman et al, 2022).…”
Section: Issue 2: Corruption In Politicsmentioning
confidence: 99%
See 3 more Smart Citations